Transformasi Perempuan dari “Liyan” ke “Diri” dalam Tiga Cerita Rakyat Kulisusu: Analisis Wacana Feminisme - La Ode Gusman Nasiru (POETIKA, 2017)
The study examined three female characters in Kulisusu folklore, each titled: Perselingkuhan Istri Lakino Lipu; Putri yang Hilang; Lagumba dan Wa Ure-Ure Ngkamagi. Three of them narrated women in prototype uniformity, in a concept that is more fluid than some kindergarten like Bawang Putih Bawang Merah or Cinderella. Fluidity mean that the liberation of women from all forms of subordination: a class polarization that took shape into archetypes dichotomous construction. The characters are identified as women who are not only clever, but also able to make decisions in determining their fate. This study will address two issues: 1) how women were originally seated as "liyan"; 2) how the plot revolves and places women as "self". Both are implicated by using the feminism discourse perspective. The review will help parents sort out stories that address the values of plurality and gender equality principles, and stories that must be abandoned for internalizing the bias in the eyes of the quality.